Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.3389/fpls.2023.1040839
|View full text |Cite
|
Sign up to set email alerts
|

Adaptations to the stressful combination of serpentine soils and Mediterranean climate drive plant functional groups and trait richness

Abstract: IntroductionPlant functional traits (FTs) are important for understanding plant ecological strategies (e.g., drought avoidance), especially in the nutrient-poor soils of serpentine ecosystems. In the Mediterranean areas, such ecosystems are characterized by climatic factors (e.g., summer drought) that exert a filtering effect.Material and MethodsIn our study, we analyzed 24 species with varying serpentine affinity, from strictly serpentine plants to generalist plants, from two ultramafic shrublands in southern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 83 publications
0
1
0
Order By: Relevance
“…In a rhizotron experiment, individuals of O. lesbiaca from Ni rich soils (Ampeliko) proved to be more tolerant in terms of root growth relative to those from sites with lower nickel content (Loutra), as Ni-induced nitric oxide accumulation was observed in their root tips along with a decrease in the degree of protein tyrosine nitration (Feigl et al 2020). The difference in traits of the O. lesbiaca could also be linked to high resistance to low nutrient and water availability (Kazakou et al 2008; Harrison et al 2017), as species strictly restricted to serpentine habitats are found to have higher drought tolerance than more generalist Mediterranean species (Hidalgo-Triana et al 2023). The link between metal hyperaccumulation and drought resistance has been hypothesized (Severne, 1974): excess nickel in cells can act as an osmoticum, reducing the water potential in plants (Baker & Walker, 1989), and allowing photosynthesis to continue during drought conditions (Fitter & Hay, 1981).…”
Section: Discussionmentioning
confidence: 99%
“…In a rhizotron experiment, individuals of O. lesbiaca from Ni rich soils (Ampeliko) proved to be more tolerant in terms of root growth relative to those from sites with lower nickel content (Loutra), as Ni-induced nitric oxide accumulation was observed in their root tips along with a decrease in the degree of protein tyrosine nitration (Feigl et al 2020). The difference in traits of the O. lesbiaca could also be linked to high resistance to low nutrient and water availability (Kazakou et al 2008; Harrison et al 2017), as species strictly restricted to serpentine habitats are found to have higher drought tolerance than more generalist Mediterranean species (Hidalgo-Triana et al 2023). The link between metal hyperaccumulation and drought resistance has been hypothesized (Severne, 1974): excess nickel in cells can act as an osmoticum, reducing the water potential in plants (Baker & Walker, 1989), and allowing photosynthesis to continue during drought conditions (Fitter & Hay, 1981).…”
Section: Discussionmentioning
confidence: 99%